Integrating “secularism and fundamentals of religious studies” into the mandatory curriculum of secondary education in Almaty, Kazakhstan: a case study (Eurasian Journal of Religious Studies, 2023)
This research delves into the implementation and impact of the subject “Secularism and Fundamentals of Religious Studies” within the educational framework of Kazakhstan, specifically within Almaty, a pivotal urban center in the country. Kazakhstan, evolving rapidly since gaining independence, faces a surge in religious institutions and a dearth of qualified personnel, including educators in religious studies. Against a backdrop of religious diversity within a secular society, this study assesses the subject's role in shaping perceptions, countering extremism, and fostering religious literacy among students. The methodology involved surveys and discussions with 63 educators from diverse secondary schools in Almaty. The study gauged perceptions, evaluated subject materials, and solicited suggestions for improvement. Key objectives included assessing comprehension of subject goals, identifying pertinent subject matter, analyzing student perspectives, understanding teachers' needs for resources, and gathering suggestions for subject enhancement. The subject aims to cultivate religious tolerance, prevent involvement in destructive religious associations, familiarize students with world religions and their history, and enhance religious literacy. The primary textbook, “Secularism and Fundamentals of Religious Studies” by Kenzhetayev D., supplemented occasionally by “Fundamentals of Religious Studies” by G. Yessim, serves as a cornerstone.
Keywords: Religious Studies; Religious Education; Secularism; Kazakhstan; Tolerance